2016
DOI: 10.3998/ark.5550190.p009.593
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in copper nanoparticle-catalyzed synthesis of 1,4-disubstituted 1,2,3-triazoles in water

Abstract: The Cu(I)-catalyzed 1,3-dipolar cycloaddition between terminal alkynes and organic azides generating 1,4-disubstituted 1,2,3-triazoles has attracted considerable attention owing to its consistency, specificity, and biocompatibility. Copper nanoparticles supported on various supports such as agarose, cellulose, chitosan, charcoal, activated carbon, silica gel, aminoclay, polymer support like poly(styrene-co-maleimide) (SMI) and polyvinylpyrrolidone (PVP) have been utilized as heterogeneous catalyst for the synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…The reaction mechanism of copper-catalyzed triazole ring formation involving one copper atom is shown in Figure 3. [60][61][62][63] Copper acetylide is formed at the outset, and this is followed by coordination of the copper ion with the organic azide. This complex undergoes a cycloaddition to form a six-membered ring that converts to a five-membered ring forming a copper triazolide intermediate.…”
Section: Investigations Of the Reaction Mechanismmentioning
confidence: 99%
“…The reaction mechanism of copper-catalyzed triazole ring formation involving one copper atom is shown in Figure 3. [60][61][62][63] Copper acetylide is formed at the outset, and this is followed by coordination of the copper ion with the organic azide. This complex undergoes a cycloaddition to form a six-membered ring that converts to a five-membered ring forming a copper triazolide intermediate.…”
Section: Investigations Of the Reaction Mechanismmentioning
confidence: 99%
“…Additionally, the covalent grafting of active organic molecules like trimethoxysilane derivatives to inorganic networks such as HAP, silica and other mesoporous materials can provide the proper sites for chelation with metal species [13]. In this regard, Cu (I) salts are widely used in OIHCs structure due to the excellent performance of Cu(I) catalyst in 'Click' Huisgen azide-alkyne cycloaddition [14]. Active Cu (I) as a catalyst has an undeniable role in the regioselectivity of the Huisgen cycloaddition reaction and merely acquires 1,4-disubstituted 1,2,3-triazoles isomers.…”
Section: Introductionmentioning
confidence: 99%
“…An initial demonstration of this was exemplified by generating an azo compound that was directly trapped intramolecularly by a diene in situ in excellent yield. 12,13 Although it has been recently shown that certain copper complexes can be used as mild oxidation systems for a number of related reactions, [14][15][16][17][18][19][20] the copper-catalyzed aerobic oxidation of hydrazines and hydrazides to the corresponding azo compounds remains largely unexplored, with one example back in 1948 21 using catalytic CuBr and di-tert butyldiaziridinone as oxidant was reported, however, the resulting azobenzene did not undergo HDA trapping. 22 It has also been recently reported that a CuI-DMAP system oxidizes di-tert-butylhydrazodicarboxylate to the corresponding azodicarboxylate which was used in situ to dehydrogenate 1,2,3,4-tetrahydroquinolines.…”
Section: Introductionmentioning
confidence: 99%